Antenatal and neonatal screening - Leck, Ian.; Wald, Nicholas J. (Oxford : Oxford University Pres, 2000)
This work provides an up-to-date evaluation of antenatal and neonatal screening. Each disorder is defined and the screening tests used are analysed quantitatively. Guidance is given on how screening should be conducted while research needs are covered.
Previous ed.: 1984.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Prenatal diagnosis; Infants -- Diseases -- Diagnosis; Pregnancy -- Complications -- Diagnosis